Pengembangan E-Modul Berbantuan Heyzine Flipbook pada Materi Aku dan Kebutuhanku - Dwi Oktaviani; Rais Hidayat; Irvan Permana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science and social studies (IPAS) instruction in Grade IV-A of SDN Cimpaeun 3, Depok City, still relies mainly on printed textbooks, while the use of digital technology remains limited, resulting in suboptimal student engagement and learning outcomes. This study aims to develop, validate, and test the effectiveness of a Heyzine Flipbook-assisted e-module on the topic of "Aku dan Kebutuhanku" (Me and My Needs) to improve elementary students' learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects consisted of one media expert, one linguist, one material expert, one fourth-grade teacher, and 26 fourth-grade students of SDN Cimpaeun 3, Depok City. Data were collected through observation, interviews, validation questionnaires, response questionnaires, and pretest-posttest scores, then analyzed using qualitative descriptive and quantitative techniques. The results show that the e-module achieved a "Very Feasible" category, with validation scores of 94.67% from the media expert, 100% from the linguist, 96% from the lecturer material expert, and 98.67% from the teacher material expert. Teacher response reached 96% and student response 88.46%, both categorized as "Very Good". The product's effectiveness was demonstrated by an increase in students' average scores from 67.50 in the pretest to 93.08 in the posttest, with an N-Gain value of 0.79 (high category). These findings confirm that the Heyzine Flipbook-assisted e-module is feasible, practical, and effective as a digital teaching material for IPAS learning in elementary schools.